2019
DOI: 10.1093/glycob/cwz007
|View full text |Cite
|
Sign up to set email alerts
|

IgA1 hinge-region clustered glycan fidelity is established early during semi-ordered glycosylation by GalNAc-T2

Abstract: GalNAc-type O-glycans are often added to proteins post-translationally in a clustered manner in repeat regions of proteins, such as mucins and IgA1. Observed IgA1 glycosylation patterns show that glycans occur at similar sites with similar structures. It is not clear how the sites and number of glycans added to IgA1, or other proteins, can follow a conservative process. GalNActransferases initiate GalNAc-type glycosylation. In IgA nephropathy, an autoimmune disease, the sites and O-glycan structures of IgA1 hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 66 publications
(126 reference statements)
2
7
0
Order By: Relevance
“…The hinge region of IgA1 contained more exposed GalNAc residues in patients with IgAN than in healthy individuals (73,74), which may be explained by the relative insufficiency of Gal residues compared with GalNAc residues. Recently, Stewart et al have shown that GALNT2 is a critical determinant of the number and pattern of O-glycans added to the hinge region of IgA1 molecules (75). Therefore, the ratio of C1GALT1/GALNT2 likely determines the O-glycan composition of IgA1 molecules, and our results support this hypothesis.…”
Section: Table 2 Association Of Fluorescence Intensities Of Intrarensupporting
confidence: 88%
“…The hinge region of IgA1 contained more exposed GalNAc residues in patients with IgAN than in healthy individuals (73,74), which may be explained by the relative insufficiency of Gal residues compared with GalNAc residues. Recently, Stewart et al have shown that GALNT2 is a critical determinant of the number and pattern of O-glycans added to the hinge region of IgA1 molecules (75). Therefore, the ratio of C1GALT1/GALNT2 likely determines the O-glycan composition of IgA1 molecules, and our results support this hypothesis.…”
Section: Table 2 Association Of Fluorescence Intensities Of Intrarensupporting
confidence: 88%
“…Humans express 20 isoforms of ppGalNAc-Ts, among which ppGalNAc-T1, T2, T3, T4, T6, and T9 are expressed in IgA1-producing B cells ( Gerken et al., 2013 ; Iwasaki et al., 2003 ). Our in vitro studies demonstrated that pre-existing glycans affect sites of GalNAc attachment by GalNAc-Ts, as well as subsequent activity of other glycosyltransferases ( Stewart et al., 2019 , 2020 ). This study suggested that the expression or activity of ppGalNAc-Ts may be altered in IgA1-producing cells of patients with IgAN, resulting in secretion of IgA1 with under-glycosylated HR.…”
Section: Discussionmentioning
confidence: 66%
“…Follow-up studies have focused on the sequential addition of glycosites to the mucin domain by various glycosyltransferases including GalNAc-T2, GalNAc-T14, core 1 β1,3-galactosyltransferase1 (C1GalT1), ST6GalNAc2, and ST3Gal1. While this work was not necessarily focused on the site-specific analysis of the hinge region, the authors were able to identify eight sites of GalNAcylation in a time and enzyme resolved manner. , Finally, Takahashi and colleagues investigated an O-glycanase, which removes GalNAc-Gal glycans, in the analysis of glycopeptides in the IgA hinge region. In two separate analyses, the authors digested with (a) sialidase and trypsin or (b) an IgA protease, sialidase, O-glycanase, and trypsin .…”
Section: Mucin-domain Glycoproteomics: Examples From the Literaturementioning
confidence: 99%